Analysis of MSME Halal Product Exports in The South Sulawesi Province - Ulfah, Indar Fauziah; Pangestu, Hengky Pratika; Hadziq, M. Fuad (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
The Muslim population has now increased to 24.7 percent of the total global population, and this number is predicted to continue to grow to 30 percent in 2050. The increase in the number of Muslims is in line with growth in consumption and production in the world halal market. Some non-Muslim countries have started to have their projections for the halal industry. What is interesting in the haalal industry in the form of halal food and drinks is that efforts are being made to obtain halal certificates to market their products. Each country has its policy regarding halal certification; this creates challenges for the halal industry, which requires that every product, when sold, comply with Islamic law's provisions. In this article, SWOT Analysis will be the theoretical framework for analyzing qualitative data from interviews, observations, or case studies. These data help evaluate internal (strengths and weaknesses) and external (opportunities and threats) factors that influence MSME (Micro Smile Medium Entrepreneur) exports of halal products in South Sulawesi Province. The finding of this research is there is potential for significant growth in the export of halal products for MSMEs in South Sulawesi. Still, several obstacles are faced, including limited access to global markets, lack of information and knowledge about export requirements, and limited resources and production capabilities. Strategies to increase exports of halal products for MSMEs in South Sulawesi Province, namely improving product quality, obtaining internationally recognized halal certification, improving marketing and promotions, developing business partnerships, and utilizing digital technology.